Pengaruh Pemeriksaan dan Pengawasan Keuangan Daerah Terhadap Kinerja Penyelenggaraan Pemerintah Daerah (Studi Empiris pada Pemerintah Kabupaten/Kota di Banten) - Mohamad Husni; Riyanthi Idayu (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The implementation and supervision of regional finances is the most important part in improving the performance of local government administration. This study aims to determine the effect of regional financial inspection and supervision on the performance of local government administration in the city and district of Banten. The population in this study were all local governments in Banten. A sample of 34 people consisting of members of the Banten Representative BPK with purposive sampling technique. The data analysis technique used multiple regression testing and hypothesis testing. The results of this study indicate that (1) Regional Financial Audit has a significant effect on the performance of the Banten Provincial Government, (2) Financial management supervision has a significant effect on the performance of the Banten Provincial Government, (3) Regional financial audit and financial management supervision has a significant effect on Government performance. Area.